2010
DOI: 10.1007/s10750-010-0460-z
|View full text |Cite
|
Sign up to set email alerts
|

Fight or flight: an investigation of aggressive behavior and predator avoidance in two populations of blue crabs (Callinectes sapidus Rathbun) in New Jersey

Abstract: Recent literature has suggested aggression may be context dependent. The purpose of this investigation was to examine aggressive and predator avoidance behaviors in juvenile blue crabs of two populations. Furthermore, we wanted to determine whether aggression persisted into the adult stages. Juvenile blue crabs collected from an impacted estuary, the Hackensack Meadowlands (HM), were found to attack a threatening stimulus significantly more often (70%) than conspecifics from a less impacted estuary (Tuckerton-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Larger blue crabs behave aggressively toward conspecifics (CLARK et al 1999, REICHMUTH et al 2011, and might also be aggressive toward other species. We speculate that the presence of the other, larger Callinectes species such as C. danae (SANT'ANNA et al 2012a) in the estuary-bay complex may influence the distribution of C. ornatus, combined with the euryhalinity characteristic of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Larger blue crabs behave aggressively toward conspecifics (CLARK et al 1999, REICHMUTH et al 2011, and might also be aggressive toward other species. We speculate that the presence of the other, larger Callinectes species such as C. danae (SANT'ANNA et al 2012a) in the estuary-bay complex may influence the distribution of C. ornatus, combined with the euryhalinity characteristic of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have observed that juvenile organisms of Callinectes sapidus are aggressive, react to external stimuli, such as foreign objects and they are cannibals, and these behaviors persist in adult stages (Hines and Ruiz, 1995;Clark et al, 1999;Hines, 2007;Reichmuth et al, 2011). Pedetta et al (2010) It was observed that in those parasitized crabs, the agonistic behavior decreased consistent with the maturation process of the externa.…”
Section: Discussionmentioning
confidence: 95%
“…During initial establishment at a new location, densities of green crabs increase rapidly, a phenomenon often associated with higher agonistic interactions in similar crab species (Clark et al 2000;Reichmuth et al 2011). Green crabs are generalist predators (Ropes 1968;Grosholz and Ruiz 1996;Klassen and Locke 2007), capable of depleting food resources in an area before moving on to new locations.…”
Section: Time Since Establishmentmentioning
confidence: 99%
“…Although foraging success and aggression may be correlated (Reichmuth et al 2011) it is clear that they are not necessarily equivalent. For example, in a study on juvenile crab foraging, green crabs were first to the bait in competition experiments (therefore considered more successful foragers) but were less aggressive than blue crabs (Callinectes sapidus; MacDonald et al 2007).…”
Section: Time Since Establishmentmentioning
confidence: 99%